Comparison of kidney injury molecule-1, proenkephalin and presepsin as predictors of diagnostics and severity of sepsis associated acute kidney injury - Puspitasari, Sri; Semedi, Bambang Pujo; Rehatta, Nancy Margaretta; Maulydia, Maulydia; Purnomo, Windhu (Edelweiss Applied Science and Technology, 2025)
Kidney Injury Molecule-1 (KIM-1), proenkephalin, and presepsin are some of the new AKI biomarkers being explored recently. This study aims to compare the accuracy of the predictive value between urine KIM-1, proenkephalin, and presepsin on the incidence and severity of SA-AKI. Samples were taken on days 1, 3, and 7. A receiver operating curve (ROC) was generated to estimate the area under the curve (AUC) and optimal cutoff values. Sensitivity and specificity accommodate the index for validity. Comparative accuracy is determined by multivariate analysis. As predictors of SA-AKI diagnosis, urine KIM-1 on the third day has the highest AUC value during the study (AUC 0.628, sensitivity 66.7%, and specificity 57.9%, p=0.154). As predictors of SA-AKI severity on the seventh day, proenkephalin and presepsin achieved AUC 0.600 (80% sensitivity and 71.4% specificity, p value = 0.5 for proenkephalin, and sensitivity of 60% and specificity 85.7%, p = 0.471 for presepsin). A p value <0.05 is considered for statistical significance, and a 95% confidence interval is used for all assessments. Based on the results, neither urine KIM-1, proenkephalin, nor presepsin has been proven to be accurate, and more studies are needed to determine diagnostic and severity predictors of SA-AKI.